(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Ensuring good management and sustainability of natural resources is paramount for future generations to thrive and live in cleaner and safer environment. This research examines the land use/land cover changes over three decades (1990 to 2019) in Potiskum using geospatial techniques. The Land use and land cover changes of the years 2010 and 2019 showed a continuous trend of vegetation being converted to cultivated areas while cultivated areas are converted to built-up areas. The findings show significant changes in vegetation cover across the study area between 1990 and 2019. Specifically, the years 2010 and 2019 witnessed a significant reduction in vegetation cover of 38% compared to 1990 and 2000 which reveals a decrease of 14.5%. From 2000 to 2010, a decrease of 8% in the vegetation cover was found. Cumulatively, the vegetation loss in the study area was found to be 60.5% between 1990 and 2019. This is highly significant and almost irreversible due to the fragile nature of the environment. The several causative factors responsible for the vegetation loss include intensification of agricultural activities, deforestation, rapid urbanization and exponential population growth. These causative factors have led to many ecological impacts such as drought, desert encroachment, sand storm, flooding, rise in temperatures, soil erosion and rainfall variations. The research recommends afforestation and reforestation measures, legislation on sustainable utilization of natural resources, tree planting campaign and subsidies on alternative sources of energy.